A Silvan Tomkins Handbook Foundations for Affect Theory - Wilson, Elizabeth A. (University of Minnesota Press, 2020)
An accessible guide to the work of American psychologist and affect theorist Silvan Tomkins The brilliant and complex theories of psychologist Silvan Tomkins (1911-1991) have inspired the turn to affect in the humanities, social sciences, and elsewhere. Nevertheless, these theories are not well understood. A Silvan Tomkins Handbook makes his theories portable across a range of interdisciplinary contexts and accessible to a wide variety of contemporary scholars and students of affect. A Silvan Tomkins Handbook provides readers with a clear outline of Tomkins's affect theory as he developed it in his four-volume masterwork Affect Imagery Consciousness. It shows how his key terms and conceptual innovations can be used to build robust frameworks for theorizing affect and emotion. In addition to clarifying his affect theory, the Handbook emphasizes Tomkins's other significant contributions, from his broad theories of imagery and consciousness to more focused concepts of scenes and scripts. With their extensive experience engaging and teaching Tomkins's work, Adam J. Frank and Elizabeth A. Wilson provide a user-friendly guide for readers who want to know more about the foundations of affect studies.